Aesthetics, illusion of success and age interactions: disentangling effects in the closed-loop design with sham neurofeedback training - Naas, Adrian; Rohrbach, Scott; Shabestari, Payam Sadeghi; Neff, Patrick; Sonderegger, Andreas (Frontiers in Human Neuroscience, 2025)
This study examined the influence of the aesthetics of visual feedback stimuli in neurofeedback training (NFB). Previous research shows a lack of specific design standards in NFB research and its application. Beyond limited literature on continuous and intermittent feedback presentation effects, most NFB design parameters remain largely understudied. Studies in the context of interface design has pointed at possible effects of aesthetics and task difficulty, indicating an interaction effect of aesthetics on performance and perseverance in difficult task conditions. The study at hand evaluates whether similar effects emerge in the context of NFB. In order to address this question, aesthetics and NFB illusion of success were manipulated experimentally in a sham NFB study (N = 24) following a 2 × 2 within-subjects design. The main dependent variables were perseverance behavior, subjective workload, motivation, and EEG activity. Results indicated an interaction between pleasing design, illusion of success, and participant age affecting perseverance and physical demand. Alpha-1 band amplitudes were modulated by an interaction between pleasing design and age, and a main effect of the illusion of success emerged. Surprisingly, only the illusion of success variable appeared to exert a meaningful influence on the workload and motivation context. Discussing the observed results, the study partially confirms the hypothesis of aesthetics affecting the outcome when the task is difficult in the context of NFB. The relevance of the age variable is addressed, and potential effects in the context of executive functioning and technology adoption processes are considered. Results encourage further research on the topic of NFB design optimization, including verum NFB in the patient population to increase NFB therapy potential.